Genetic analysis of tumour initiation and progression in a Drosophila model of epithelial cancer - Froldi, Francesca <1984> (Alma Mater Studiorum - Università di Bologna, 2012)
Neoplastic overgrowth depends on the cooperation of several mutations ultimately leading to major rearrangements in cellular behaviour. The molecular crosstalk occurring between precancerous and normal cells strongly influences the early steps of the tumourigenic process as well as later stages of the disease. Precancerous cells are often removed by cell death from normal tissues but the mechanisms responsible for such fundamental safeguard processes remain in part elusive. To gain insight into these phenomena I took advantage of the clonal analysis methods available in Drosophila for studying the phenotypes due to loss of function of the neoplastic tumour suppressor lethal giant larvae (lgl). I found that lgl mutant cells growing in wild-type imaginal wing discs are subject to the phenomenon of cell competition and are eliminated by JNK-dependent cell death because they express very low levels of dMyc oncoprotein compared to those in the surrounding tissue. Indeed, in non-competitive backgrounds lgl mutant clones are able to overgrow and upregulate dMyc, overwhelming the neighbouring tissue and forming tumourous masses that display several cancer hallmarks. These phenotypes are completely abolished by reducing dMyc abundance within mutant cells while increasing it in lgl clones growing in a competitive context re-establishes their tumourigenic potential. Similarly, the neoplastic growth observed upon the oncogenic cooperation between lgl mutation and activated Ras/Raf/MAPK signalling was found to be characterised by and dependent on the ability of cancerous cells to upregulate dMyc with respect to the adjacent normal tissue, through both transcriptional and post-transcriptional mechanisms, thereby confirming its key role in lgl-induced tumourigenesis. These results provide first evidence that the dMyc oncoprotein is required in lgl mutant tissue to promote invasive overgrowth in developing and adult epithelial tissues and that dMyc abundance inside versus outside lgl mutant clones plays a key role in driving neoplastic overgrowth.